Plant and soil metal concentrations in serpentine soils and their influence on the diet of extensive livestock animals - Ramalhosa, Elsa (2018)
Background: Grazing circuits and resources consumed differ strongly throughout the year and within a territory. For this reason, animals’ diet composition, as well as their exposure to metals, is variable. No studies have been performed on how habitat use affects the metal concentrations to which sheep and goats reared in serpentine soil areas are exposed. Objective: The aim of the present study was to investigate the metal exposure of grazing animals raised in a serpentine soil area of the north-east of Portugal, taking into account the spatial distribution of metal concentrations in soils and plants. Methods: The habitat use and foraging behaviour of six flocks of sheep and goats were studied. The concentrations of Ca, Mg, Mn, Cr and Ni were determined in the soils and plant species most consumed by those animals. Results: The highest Mg, Mn, Cr and Ni concentrations were found in the soils of the ultramafic complex. Ni concentrations above the recommended threshold for agricultural soils (30 μg/g) were found in some sites. A positive correlation between Ni concentration in soils and plants was found (0.634). Ni concentrations higher than 10 μg/g were found in some samples of the following plant species: Sorghum × drummondii (Steud.) Millsp. & Chase,Quercus rotundifolia Lam., Cytisus multiflorus (L’Hér.) Sweet, Cistus ladanifer L. and Erica scoparia L. Significant differences (p ≤ 0.05) in metal concentrations of the plants most consumed by each flock were observed. Conclusion: Grazing circuits have an important role in the metal exposure of animals raised in this serpentine soil area.